Inovasi Teknologi dalam Kebijakan Lingkungan di Daerah Kabupaten Pelalawan: Peluang dan Tantangan - Rizka Gusnia Ananda (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study examines technological innovation in environmental policy in Pelalawan Regency, Riau, a region known for its abundant forest resources but facing serious environmental pressures due to forest degradation, land fires, and industrial pollution. The primary objective of this research is to identify policy innovations that can enhance environmental management and support sustainable development that harmonizes economic and ecological aspects. The methodology employed is a qualitative approach with a case study design, involving interviews, participatory observation, and document analysis. The findings indicate that the implementation of technologies such as Internet of Things (IoT)-based air quality sensors and Geographic Information Systems (GIS) has improved the effectiveness of environmental management. However, challenges such as limited human resource capacity, uneven technological infrastructure, and bureaucratic resistance continue to hinder innovation implementation. This study recommends strengthening digital infrastructure, revitalizing the licensing system, and fostering multi-stakeholder collaboration as strategic steps toward improved environmental governance. With an inclusive and sustainable approach, Pelalawan Regency has the potential to become a model for sustainable development in Indonesia.